Rupture Model of the 5 April 2024 Tewksbury, New Jersey, Earthquake Based on Regional Lg-Wave Data - Sangwoo Han; Won-Young Kim; Jun Yong Park; Min-Seong Seo; YoungHee Kim (The Seismic Record, 2024)
On 5 April 2024, an earthquake of magnitude 4.8 occurred in Tewksbury, New Jersey. It was the largest instrumentally recorded event since 1900 in New Jersey and southern New York. Millions of people around New York City, ∼65 km east-northeast of Tewksbury, felt the shaking from the mainshock, but the epicentral area experienced no known significant property damages. We determine the focal mechanism, which is oblique faulting, and retrieve the Lg-wave relative source time functions (RSTFs) from the stations at regional distances to understand rupture processes and ground motions. Our fault-slip models well explain azimuthal variations of the RSTFs. The models show the rupture propagating toward the east-northeast (∼50° to 60°), not along the fault strike. The slip distribution on the nodal plane striking north and dipping to the east shows a slip area of 1.1 km radius with the rupture propagating down-dip. The down-dip rupture may account for the observed lack of strong shaking in the epicentral area.